2021
DOI: 10.1111/jfb.14780
|View full text |Cite
|
Sign up to set email alerts
|

Allopatric differentiation in the Enteromius anoplus complex in South Africa, with the revalidation of Enteromius cernuus and Enteromius oraniensis, and description of a new species, Enteromius mandelai (Teleostei: Cyprinidae)

Abstract: The chubbyhead barb, Enteromius anoplus, as currently described, is the most widely distributed freshwater fish in South Africa. The species occurs in almost all the major river systems across the country, with the exception of the small coastal drainages on the south coast. The use of a comprehensive data set of mitochondrial (mtDNA) cytochrome b (cyt b) sequences uncovered the presence of four distinct lineages or operational taxonomic units (OTUs) within E. anoplus: (a) the Gouritz lineage endemic to the Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…However, there are additional steps that could improve upon and update the tool, thereby supporting more effective freshwater conservation in the future. Firstly, there is an urgent need to update and resolve the taxonomy of South Africa's freshwater fishes, as there are a number of distinct genetic lineages that await formal description (Chakona et al, 2015(Chakona et al, , 2020bMartin and Chakona, 2019;Bronaugh et al, 2020;Kambikambi et al, 2021;Mazungula and Chakona, 2021;Ramoejane et al, 2021). Once the taxonomy of South Africa's freshwater fishes has been revised, the FBIS and NEST can be updated accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are additional steps that could improve upon and update the tool, thereby supporting more effective freshwater conservation in the future. Firstly, there is an urgent need to update and resolve the taxonomy of South Africa's freshwater fishes, as there are a number of distinct genetic lineages that await formal description (Chakona et al, 2015(Chakona et al, , 2020bMartin and Chakona, 2019;Bronaugh et al, 2020;Kambikambi et al, 2021;Mazungula and Chakona, 2021;Ramoejane et al, 2021). Once the taxonomy of South Africa's freshwater fishes has been revised, the FBIS and NEST can be updated accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary morphological and/or genetic data revealed that all of these species seem to represent species complexes, thus harbouring hidden species diversity. This is consistent with findings from previous studies that have uncovered considerable levels of hidden species diversity within several freshwater fish species that were previously thought to have broad distribution ranges across river basins in southern Africa ( e.g ., Chakona et al ., 2013, 2014, 2018; Chakona & Skelton, 2017; Kambikambi et al ., 2021; Maake et al ., 2014; Mazungula & Chakona, 2021) or major catchments of the Congo Basin ( e.g ., Decru et al ., 2015b, 2019; Katemo Manda et al ., 2018; Mambo Baba et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The native ichthyofauna in the Gariep Dam is generally distinct from that of the Great Fish River. Although historical data indicated close affinities in taxa such as Labeo umbratus (A. Smith, 1841) and Enteromius anoplus (Weber, 1897) between the two systems, subsequent research has shown that these also represent distinct lineages and separate species (Ramoejane et al, 2020; Kambikambi et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…This river system is known to host an ichthyofauna assemblage that comprise both native and non‐native species. The native fish assemblage included primary freshwater taxa such as Enteromius mandelai Kambikambi et al, 2021 and the endangered Sandelia bainsii Castelnau, 1861, which were mostly confined to headwater tributaries. In comparison, the mainstem comprised mostly medium‐ to large‐sized species with the upper section comprising two native species, L. umbratus and Anguilla mossambica Peters, 1852, whereas the lower section was characterized by secondary freshwater and estuarine taxa.…”
Section: Methodsmentioning
confidence: 99%